Multilinear subspace learning : dimensionality reduction of multidimensional data /: dimensionality reduction of multidimensional data. (2013) - Lu, Haiping; Plataniotis, Konstantinos N; Venetsanopoulos, A. N (Anastasios N.), 1941-
No abstract available